Ergonomics, design and reliability of body armour - Watson, Celia H. (Cranfield University, 2011)
The wearing of body amour has become a necessity for many professions and much work has gone into the optimisation of the mechanics of protection. In the present study a broader view of the effects of ergonomics, design, reliability and protection has been taken. Three background topics are examined by reference to the literature. First, as an example of the threats and injury mechanisms that prevail in modern conflicts, the effects of blast injury to the head are investigated. This is followed by a review of ergonomic test methods and is completed by a study exploring the influence of history on modern body armour design. Solutions to some of these problems are then considered. The problem of accurately measuring impact loads to the head is investigated and a rigid instrumented head form is demonstrated. This work showed that the filtering techniques derived from crash tests used in the current helmet standards are not applicable to ballistic impact events. A one day wearer trial for police armour based on typical actions carried out by police officers in the performance of their normal duties is developed and demonstrated. A mechanical flexibility test is shown to give quantitative data but a direct link between ergonomic rankings and flexibility could not be established. Reliability of both soft and hard body armour is investigated and for typical armour types it is demonstrated that a minimal deterioration takes place with time and existing inspections techniques can highlight armour that is below standard. This study has introduced measurement techniques in an attempt to quantify some of the effects investigated with the intention of using quantitative methods to improve armour design and minimise some of the negative effects of wearing body armour.